Implementasi Amaliyah Aswaja untuk Meningkatkan Sikap Religius Siswa di SD Islamiyah Magetan - Sari, Linda Permata; Maghribi, Hamdan; Arini, Yusti (Pendidikan Agama Islam STIT Palapa Nusantara, 2024)
The aim of this research is to examine the implementation of Aswaja practices at SD Islamiyah Magetan in enhancing students' religious attitudes and to identify the supporting and inhibiting factors. This study employs a qualitative case study approach. The subjects of this research include the principal, teachers, and students of SD Islamiyah Magetan. Data collection techniques used are interviews, observations, and documentation. Data analysis techniques follow the Miles and Huberman model. The results indicate that Aswaja education at SD Islamiyah Magetan is systematically and comprehensively organized, and has a significant impact on enhancing students' religious attitudes. The curriculum is designed to ensure that students not only understand but also practice the taught amaliyah according to their grade level. The religious environment at the school is also fostered through daily routines and supportive extracurricular activities. The improvement in students' religious attitudes is evident from the increased memorization of verses and prayers, student participation in religious activities, and students' awareness of worship. Supporting factors for the implementation of Aswaja practices at SD Islamiyah Magetan include the teachers' deep understanding of Aswaja teachings, a conducive religious atmosphere, and collaboration between school and home. Inhibiting factors include the lack of facilities and infrastructure, and the lack of innovative teaching methods and media. This research is expected to contribute to the enhancement of religious education at SD Islamiyah Magetan and other schools with similar religious education programs, thereby shaping students with strong religious attitudes.